Greater sage‐grouse and fences: Does marking reduce collisions? - Bryan S. Stevens; Kerry P. Reese; John W. Connelly; David D. Musil (Wildlife Society Bulletin)
Abstract Collision with infrastructure such as fences is widespread and common for many species of grouse. Greater sage‐grouse (Centrocercus urophasianus) fence‐collision has been documented and fence‐marking methods have been recommended for mitigating prairie‐grouse collision in rangeland habitats. We tested a marking method in greater sage‐grouse breeding habitat and modeled collision as a function of fence marking and control covariates, in Idaho (USA) in 2010. Our results suggested collision risk decreased with fence marking, increased with lek‐count indices of local abundance, and decreased with increasing distance from lek. We found an approximate 83% reduction in collision rates at marked fences relative to unmarked fences. Our results also suggested marking may not be necessary on all fences, and mitigation should focus on areas with locally abundant grouse populations and fence segments <2 km from known leks. Nonetheless, collision still occurred at marked fences <500 m from large leks and moving or removing fences may be necessary in some areas if management is to eliminate collision. © 2012 The Wildlife Society.